PENERAPAN UNDANG-UNDANG TINDAK PIDANA KORUPSI TERHADAP TINDAK PIDANA DIBIDANG KEHUTANAN - Ifrani Ifrani (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
In the practice occurduringthe handling corruption cases, it can be seen that the public prosecutor often encountered in the letter of indictment often use the Act 31 of 1999 jo Law No. 20 of 2001 to the other criminal offenses as criminal acts in the forestry,Law No. 20 of 2001 on Amendments to the Law No. 31 of 1999 on Corruption Eradication. In Article 14 explicitly states that the provision that: